Performance Bank BNI Syariah Di Masa Pandemi Covid-19 - Dwi Nur'aini Ihsan; Muhamad Nadratuzzaman Hosen (ITB AAS INDONESIA Surakarta, 2021)
The performance of Islamic banks during the Covid-19 pandemic has had an impact on the financial soundness of Islamic Banks. Islamic Banks in Indonesia should restructure the Financing (PYD) which results in the acquisition of revenue and net profit received by the bank. The aims of this study are to analyze the soundness of Bank BNI Syariah using the CAMEL, RGEC method, the level of cost efficiency and profitability. Then also measured the potential for BNIS bankruptcy with the Altman Z-Score model. The potential risk of bankruptcy in Islamic Banks is very possible if bank management during the Covid-19 pandemic are not carried out properly and professionally. Secondary data is used during the period 2015 to 2020 to analyze the performance of Islamic Banks before the pandemic and during the pandemic. The results of the CAMEL and RGEC analysis show that soundness conditions varied from